PEMANFAATAN POJOK LITERASI DALAM PEMBELAJARAN IPA SEBAGAI UPAYA MENINGKATKAN MINAT BACA SISWA KELAS V SDN 75 BENTANG - Putri Ratna; Wanda; Nasrah (STKIP Subang, 2025)
This study aims to describe efforts to optimize the literacy corner as a means of increasing the reading interest of fifth-grade students at SDN 75 Bentang. The background of this study is based on the low reading interest of students caused by limited reading facilities and the lack of a variety of interesting reading materials in the school environment. This study uses a qualitative approach with a descriptive method. The subjects of the study were 28 fifth-grade students at SDN 75 Bentang. Data were collected through observation, interviews, and actions. The results of the study indicate that optimal management of the literacy corner through the arrangement of a comfortable reading space, the provision of diverse reading books, and the active involvement of teachers in literacy activities has a positive effect on increasing students' reading interest. After the optimization was carried out, fifth-grade students showed increased enthusiasm in reading and actively utilized the literacy corner at the front of the class. Thus, optimizing the literacy corner has proven effective as a strategy to foster a reading culture at SDN 75 Bentang.